Determination of Three Endocrine Disruptors in Water Samples by Ultrasound-Assisted Salt-Induced Liquid-Liquid Microextraction (UA-SI-LLME) and High-Performance Liquid ChromatographyâDiode Array Detection (HPLC-DAD) - Rozaini, M.N.H. (Taylor and Francis Ltd., 2022)
Endocrine-disrupting compounds are routinely detected in environmental water. In this study, a simple and rapid sample preparation method based on ultrasound-assisted salt-induced liquid-liquid microextraction (UA-SI-LLME) followed by high performance liquid chromatographyâdiode array detection (HPLC-DAD) was developed for the determination of triclosan, triclocarban and methyl-triclosan in water. Parameters that affect the extraction efficiencyâsuch as type and mass of salt, type and volume of extraction solvent, extraction time, sample pH and sample volumeâwere studied. Under the optimized conditions, the method demonstrated linearity from 0.18 to 1000 Âµg Lâ1 with coefficients of determination R2 â¥ 0.9899, limits of detection from 0.05 to 0.2 Âµg Lâ1, and good recoveries (> 70) with relative standard deviations < 10. The method was applied for the determination of triclosan, triclocarban, and methyl-triclosan in swimming pool, lake, and wastewater. The greenness of the method was quantified using the Analytical Eco-Scale Index. Â© 2022 Taylor & Francis Group, LLC.